Highly polarization sensitive photodetectors based on quasi-1D titanium trisulfide (TiS3). (8th March 2018) - Liu, Sijie; Xiao, Wenbo; Zhong, Mianzeng; Pan, Longfei; Wang, Xiaoting; Deng, Hui-Xiong; Liu, Jian; Li, Jingbo; Wei, Zhongming
Abstract: Photodetectors with high polarization sensitivity are in great demand in advanced optical communication. Here, we demonstrate that photodetectors based on titanium trisulfide (TiS3 ) are extremely sensitive to polarized light (from visible to the infrared), due to its reduced in-plane structural symmetry. By density functional theory calculation, TiS3 has a direct bandgap of 1.13 eV. The highest photoresponsivity reaches 2500 A W −1 . What is more, in-plane optical selection caused by strong anisotropy leads to the photoresponsivity ratio for different directions of polarization that can reach 4:1. The angle-dependent photocurrents of TiS3 clearly display strong linear dichroism. Moreover, the Raman peak at 370 cm −1 is also very sensitive to the polarization direction. The theoretical optical absorption of TiS3 is calculated by using the HSE06 hybrid functional method, in qualitative agreement with the observed experimental photoresponsivity.